2023
DOI: 10.1111/jocn.16679
|View full text |Cite
|
Sign up to set email alerts
|

Developing nurse‐sensitive outcomes in acute inpatient mental health settings—A systematic review

Abstract: BackgroundWhile nurse‐sensitive outcomes (NSOs) are well established in numerous health settings, to date there is no indicator suite of NSOs for inpatient mental health settings.AimTo assess the relationship between nursing variables and patient outcomes in acute inpatient mental health settings to determine which outcomes can be used as indicators of the quality of nursing care.MethodsDatabases accessed were CINAHL, MEDLINE, PsycINFO and EMBASE, last searched in May 2022. The review followed the 2020 PRISMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
(186 reference statements)
0
3
0
1
Order By: Relevance
“…These results were unclear, and more studies are needed to draw these conclusions. A recent review of literature also recommended further studies to establish the role of staff related factors and their association with increased risks in mental health settings (Ngune et al, 2023). Our review also showed, there was contradictory evidence about time of falls with some studies indicating that late nights to early mornings (An et al, 2009; Seeherunwong et al, 2022) were risky times and other study daytime (Chan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These results were unclear, and more studies are needed to draw these conclusions. A recent review of literature also recommended further studies to establish the role of staff related factors and their association with increased risks in mental health settings (Ngune et al, 2023). Our review also showed, there was contradictory evidence about time of falls with some studies indicating that late nights to early mornings (An et al, 2009; Seeherunwong et al, 2022) were risky times and other study daytime (Chan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion of both studies highlights the need to reach international consensus to guarantee minimum standards for actions or at least national guidelines. In mental health nursing, a systematic literature review assessed outcomes that could generate quality indicators, concluding that the studies were of variable quality and that the seven indicators proposed at the conclusion of the review should be integrated into administrative data ( 12 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies re‐examine the issue of violence in acute mental healthcare (Jenkins, Quigg, et al, 2022; Weltens et al, 2021) and it is essential that its occurrence and impact is reduced if inpatient units are to be satisfying places to work, as well as to receive care. Ngune et al (2023) highlight robust evidence for aggression, restraint use and seclusion to be regarded as nurse sensitive outcomes in acute mental health. We call for renewed focus on the monitoring of changes in nurse variables and their impact on client outcomes as well as staff retention.…”
Section: Potential Solutionsmentioning
confidence: 99%